2019
DOI: 10.1111/imr.12765
|View full text |Cite
|
Sign up to set email alerts
|

STING pathway agonism as a cancer therapeutic

Abstract: The fact that a subset of human cancers showed evidence for a spontaneous adaptive immune response as reflected by the T cell‐inflamed tumor microenvironment phenotype led to the search for candidate innate immune pathways that might be driving such endogenous responses. Preclinical studies indicated a major role for the host STING pathway, a cytosolic DNA sensing pathway, as a proximal event required for optimal type I interferon production, dendritic cell activation, and priming of CD8+ T cells against tumor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
183
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 243 publications
(203 citation statements)
references
References 150 publications
(307 reference statements)
5
183
0
Order By: Relevance
“…Activation of the cGAS-STING pathway, via direct (STING agonist, oncolytic virus) and indirect (radiation, PARP inhibitors) approaches, is an emerging immune adjuvant treatment approach 8, 11 . With several promising pre-clinical findings across an array of cancer models, recent reports including ours have confirmed the immune sensitizing effect of STING pathway activation thus improving response to conventional chemotherapy and novel ICB 12 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Activation of the cGAS-STING pathway, via direct (STING agonist, oncolytic virus) and indirect (radiation, PARP inhibitors) approaches, is an emerging immune adjuvant treatment approach 8, 11 . With several promising pre-clinical findings across an array of cancer models, recent reports including ours have confirmed the immune sensitizing effect of STING pathway activation thus improving response to conventional chemotherapy and novel ICB 12 .…”
Section: Discussionmentioning
confidence: 99%
“…We demonstrated that a non-inflamed pre-existing T helper type I tumor immune microenvironment (TIME), decreased expressions of type I interferon (IFN1) genes and STAT1 protein, low density of TILs associated with poor response to chemotherapy 10 . Strategies attempting to transform these immunologically cold tumors to hot, thus improving therapeutic response through IFN1 activation, have recently garnered tremendous interest across solid tumours 8, 11 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is also believed that STING agonists might be used in antiviral therapies. One of the potential advantages of these new molecules is that they can be transported through blood ( 186 ). This new immunotherapy drug greatly enhanced the adaptive immune function.…”
Section: Therapeutic Agents Targeting Stingmentioning
confidence: 99%
“…The STING pathway has been shown to mediate protective immune defense against infection through a wide range of DNA comprising microbial pathogens. The mitochondrial DNA is similar to that of microbial DNA, and has attained great attention as a mediator of innate immunity via the STING pathway [49,50]. STING protein is activated by direct interaction with cytosolic DNA, which is usually derived from intracellular viruses or bacteria or cyclic GMP-AMP synthetase and so on.…”
Section: Mitochondrial Dna As a Stimulator Of Interferon Signalingmentioning
confidence: 99%